2022
DOI: 10.1177/07334648221129858
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness is Associated With Lower Coping Self-Efficacy Among Older Adults

Abstract: To address the gap of lacking research on the association between coping self-efficacy and loneliness, this study examined this relationship to inform future research and intervention on loneliness. Using data from 151 community-dwelling older adults ages 65 and older, we estimated multivariate logistic regression models with age, race/ethnicity, sex, body mass index, chronic disease composite score, social support, coping self-efficacy, and depression symptoms. Loneliness was reported in 32.1% of participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…It is plausible that being confident about one’s ability to cope with the demands, tasks and challenges of life facilitates social engagement. A recent study conducted among 150 US community-dwelling older adults aged 65 years and older found that coping self-efficacy was associated with decreased odds of loneliness [ 38 ]. Other studies have also reported that greater general self-efficacy is associated with decreased loneliness [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that being confident about one’s ability to cope with the demands, tasks and challenges of life facilitates social engagement. A recent study conducted among 150 US community-dwelling older adults aged 65 years and older found that coping self-efficacy was associated with decreased odds of loneliness [ 38 ]. Other studies have also reported that greater general self-efficacy is associated with decreased loneliness [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Others emphasise the importance of social connectivity in particular, and call for opportunities for social interaction to be embedded in the structure of group activities beyond that which may occur incidentally ( 134 ). This is important for combatting loneliness which is negatively associated with cardiovascular and autoimmune conditions, mental health, cognitive function, risk of dementia ( 135 ) and coping self-efficacy ( 31 ). Our interviewees were clear that RIPE Dance classes were uplifting and validating.…”
Section: Discussionmentioning
confidence: 99%
“…As Coaten argues, “The extent to which one is grounded in the lived-body experience affects one’s perceptions, understandings and sense of relatedness to the world” [9:677]. This may partly explain the emotional impact of expression through dance movement ( 11 , 31 ) which can enhance feelings of joy, energy, strength ( 29 ), empowerment, pride and determination ( 32 ). The interoceptive accuracy associated with heightened body awareness through dance may also positively impact wellbeing, empathy, altruism, emotional resilience and efficient decision-making ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nieboer et al (48) examined the relationship between self-management skills, selfefficacy beliefs, and loneliness in elderly subjects, showing that selfefficacy is a protective factor against emotional loneliness. Lee et al (49) also found a negative association between coping self-efficacy, the confidence to overcome challenges using social support, and loneliness in a study of 151 subjects aged 65 and older. They conducted a group comparison between subjects who felt lonely and subjects who did not and came to the following conclusions: the chronic disease symptoms was higher in the group of subjects feeling lonely than in the non-lonely control group.…”
Section: Introductionmentioning
confidence: 94%